A STUDY ON SCIENCE FICTION CHARACTERISTICSIN THE HOST NOVEL AND ENDER’S GAME NOVEL - ANGGRAINI, ESTY RAHAYU (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Science Fiction, Characteristics, Study of Genre.Science fiction is a kind of literary works that is dealing with science and technology. Science fiction talks how science and the advance of technology can affect the world. Just like the other kind of literary works, science fiction surely has their own characteristics or identifying mark to distinguish each other. Some of science fiction characteristics are aliens, robots, space and time travel and so on.This study is conducted to identify the characteristics of science fiction characteristics in The Host novel and Ender’s Game novel by using structuralism approach, combination of David Seed’s book, Jones theory from James and Mendlesohn’s book, Hellekson theory from Bould et al’s book, and Botting theory from Seed’s book as the main reference for identifying the characteristics of science fiction. This study uses two novels, which are The Host novel and Ender’s Game novel as the object of the study. The objective of the study is to track the manifestation of science fiction characteristics in The Host novel from Stephenie Meyer and Ender’s Game novel from Orson Scott Card.There are five characteristics of science fiction that are found in The Host novel and Ender’s Game novel.  The five characteristics are aliens, technology, spaceship, space opera, apocalyptic and ecology aspect. There are similarities and differences manifestation in each science fiction characteristics. The manifestation of science fiction characteristics in these two novels are found through characters, plot and setting.The writer suggests the next researchers to digs up more about apocalyptic concept in these two novels by using structuralism approach. Considering that apocalyptic is an expression of visions in science fiction, and because The Host novel and Ender’s Game novel also shows about the apocalyptic aspect.